APF530 (granisetron injection extended-release) in a three-drug regimen for delayed CINV in highly emetogenic chemotherapy. (June 2016) - Schnadig, Ian D; Agajanian, Richy; Dakhil, Christopher; Gabrail, Nashat Y; Smith, Robert E; Taylor, Charles; Wilks, Sharon T; Schwartzberg, Lee S; Cooper, William; Mosier, Michael C; Payne, J Yvette; Klepper, Michael J; et al.
Aim: APF530, extended-release granisetron, provides sustained release for ≥5 days for acute- and delayed-phase chemotherapy-induced nausea and vomiting (CINV). We compared efficacy and safety of APF530 versus ondansetron for delayed CINV after highly emetogenic chemotherapy (HEC), following a guideline-recommended three-drug regimen.Methods: HEC patients received APF530 500 mg subcutaneously or ondansetron 0.15 mg/kg intravenously, with dexamethasone and fosaprepitant. Primary end point was delayed-phase complete response (no emesis or rescue medication).Results: A higher percentage of APF530 versus ondansetron patients had delayed-phase complete response (p = 0.014). APF530 was generally well tolerated; treatment-emergent adverse event incidence was similar across arms, mostly mild-to-moderate injection-site reactions.Conclusion: APF530 versus the standard three-drug regimen provided superior control of delayed-phase CINV following HEC.ClinicalTrials.gov : NCT02106494.